Revelation and misunderstanding: Buton millenarianism and the interchange of cosmological tropes in North Seram, Maluku, Indonesia - Riyanto, Geger (Indonesia and the Malay world, 2020)
This article considers the millenarian disposition among the Buton of North Seram sub-district, Maluku. Particular focus is paid to how the Buton interpret their inclusion in indigenous cosmologies, given their current precarious and humiliating existence. In Maluku, the Buton have long been regarded as lower-class people, outsiders who are excluded from local cultural schematics and are both socially and legally vulnerable. Instead of simply seeing their aspiration for a new and perfect social order as something springing from their desire to end their predicament, and rather than viewing their belief as something invented for this end, I suggest that the incongruent communication of cosmological tropes is important in the formation of their millenarian framework. The Buton understand the presence of their mythical representations in the indigenous cosmologies as evidence of the original order, which inspires them to believe that the Seram people are concealing the truth and that its revelation will upturn the current oppressive order. For the often referred Seram communities, however, the inclusion of Buton mythical representations is a way of assimilating a powerful, dangerous stranger and perpetuating the wholeness of their cosmology. The emphasis on the productivity of the misunderstanding rather than the creative act of expanding symbolic frameworks helps explain the peculiar relationality which grounds Buton millenarianism.
Gesehen am 09.08.2024